The role of the substituted group on competitive formation of ansa and spiro isomers - Palabiyik, Duygu; Balci, Ceylan Mutlu; Besli, Serap (Elsevier Science Sa, 2019)
In here, a systematic study on regioisomer selectivity in the nucleophilic substitution reactions of the cyclotriphosphazene and some its derivatives, N3P3Cl4R2 [R-2 = Cl (1a); (OCH2(CF2)(2)CH2O) (1b); (OCH2CH2CH2O) (1c); NHPh (1d); (OCH2CH2CH2NH) (1e) and NHBut (1f)] with 1,3-propanediol has been performed. The compounds 1a-f were reacted with the 1,3-propanediol in THF solution at 1:1 mole ratio in the presence of two different bases, NaH and Et3N. The relative amounts of isomeric products, spiro and ansa were established quantitatively from the P-31 NMR spectra of the reaction mixtures. The products were separated and characterized by elemental analysis, mass spectrometry, H-1 and P-31 NMR spectroscopy. Crystal structures of 2b, 3b, 2e and 2f have been characterized by X-ray crystallography. Although the amount of the ansa product decreased with the increase of the electron releasing capacity of R-2 group, it formed in all the reactions in which the sodium salt of diol was used.
Keywords: Cyclophosphazene; Regioisomer; Spiro; Ansa